Context-dependent hyperactivity in syngap1a and syngap1b zebrafish models of SYNGAP1-related disorder - Sumathipala, Sureni H.; Khan, Suha; Kozol, Robert A.; Araki, Yoichi; Syed, Sheyum; Huganir, Richard L.; Dallman, Julia E. (Frontiers in Molecular Neuroscience, 2024)
Background and aimsSYNGAP1-related disorder (SYNGAP1-RD) is a prevalent genetic form of Autism Spectrum Disorder and Intellectual Disability (ASD/ID) and is caused by de novo or inherited mutations in one copy of the SYNGAP1 gene. In addition to ASD/ID, SYNGAP1 disorder is associated with comorbid symptoms including treatment-resistant-epilepsy, sleep disturbances, and gastrointestinal distress. Mechanistic links between these diverse symptoms and SYNGAP1 variants remain obscure, therefore, our goal was to generate a zebrafish model in which this range of symptoms can be studied.MethodsWe used CRISPR/Cas9 to introduce frameshift mutations in the syngap1a and syngap1b zebrafish duplicates (syngap1ab) and validated these stable models for Syngap1 loss-of-function. Because SYNGAP1 is extensively spliced, we mapped splice variants to the two zebrafish syngap1a and b genes and identified mammalian-like isoforms. We then quantified locomotory behaviors in zebrafish syngap1ab larvae under three conditions that normally evoke different arousal states in wild-type larvae: aversive, high-arousal acoustic, medium-arousal dark, and low-arousal light stimuli.ResultsWe show that CRISPR/Cas9 indels in zebrafish syngap1a and syngap1b produced loss-of-function alleles at RNA and protein levels. Our analyses of zebrafish Syngap1 isoforms showed that, as in mammals, zebrafish Syngap1 N- and C-termini are extensively spliced. We identified a zebrafish syngap1 α1-like variant that maps exclusively to the syngap1b gene. Quantifying locomotor behaviors showed that syngap1ab mutant larvae are hyperactive compared to wild-type but to differing degrees depending on the stimulus. Hyperactivity was most pronounced in low arousal settings, and hyperactivity was proportional to the number of mutant syngap1 alleles.LimitationsSyngap1 loss-of-function mutations produce relatively subtle phenotypes in zebrafish compared to mammals. For example, while mouse Syngap1 homozygotes die at birth, zebrafish syngap1ab−/− survive to adulthood and are fertile, thus some aspects of symptoms in people with SYNGAP1-Related Disorder are not likely to be reflected in zebrafish.ConclusionOur data support mutations in zebrafish syngap1ab as causal for hyperactivity associated with elevated arousal that is especially pronounced in low-arousal environments.